Systematic Review of Studies on Subliminal Exposure to Phobic Stimuli: Integrating Therapeutic Models for Specific Phobias - Frumento, Sergio; Menicucci, Danilo; Hitchcott, Paul Kenneth; Zaccaro, Andrea; Gemignani, Angelo (Frontiers in Neuroscience, 2021)
We systematically review 26 papers investigating subjective, behavioral, and psychophysiological correlates of subliminal exposure to phobic stimuli in phobic patients. Stimulations were found to elicit: 1) cardiac defence responses, 2) specific brain activations of both subcortical (e.g., amygdala) and cortical structures, 3) skin conductance reactions, only when stimuli lasted >20ms and were administered with intertrial interval >20 seconds. While not inducing the distress caused by current (supraliminal) exposure therapies, exposure to subliminal phobic stimuli still results in successful extinction of both psychophysiological and behavioral correlates: however, it hardly improves subjective fear. We integrate those results with recent bifactorial models of emotional regulation, proposing a new form of exposure therapy whose effectiveness and acceptability should be maximized by a preliminary subliminal stimulation.